2016
DOI: 10.1007/s10815-016-0832-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pregnancy outcomes in donor egg frozen embryo transfer (FET) cycles following preimplantation genetic screening (PGS): a single center retrospective study

Abstract: PurposeThis study aims to test the hypothesis, in a single-center retrospective analysis, that live birth rates are significantly different when utilizing preimplantation genetic screening (PGS) compared to not utilizing PGS in frozen–thawed embryo transfers in our patients that use eggs from young, anonymous donors. The question therefore arises of whether PGS is an appropriate intervention for donor egg cycles.MethodsLive birth rates per cycle and live birth rates per embryo transferred after 398 frozen embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
(34 reference statements)
1
20
1
Order By: Relevance
“…Coates et al (26) performed a retrospective study comparing birth outcomes in patients using PGS versus no PGS in the donor egg population and found that PGS significantly improved live birth rates with double ETs, but birth rates were not significantly different when single ET was performed. In their study, they used aCGH and NGS for PGS, and they did not perform a head-to-head comparison of the two modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Coates et al (26) performed a retrospective study comparing birth outcomes in patients using PGS versus no PGS in the donor egg population and found that PGS significantly improved live birth rates with double ETs, but birth rates were not significantly different when single ET was performed. In their study, they used aCGH and NGS for PGS, and they did not perform a head-to-head comparison of the two modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even in the most favorable patient population with lowest incidence of aneuploidy, PGT-A can hypothetically have considerable impact. In spite of the STAR study results (discussed above), there is evidence from observational studies that PGT-A is beneficial in young, good-prognosis patients: It improved outcomes with young oocytes from egg donation cycles [161], and increased live birth rates per cycle in a statistically significant fashion in patients younger than 35 [162].…”
Section: Which Patients and Embryos Should Be Offered Pgt-a?mentioning
confidence: 89%
“…Because they collected data from multiple IVF clinics and each clinic used different biopsy methods, which may make it difficult to analyze these factors. In the present study, to minimize the effects of maternal age-related aneuploidy formation in the embryos [6,[13][14][15][17][18][19][20], we also used donor egg IVF cycles to examine whether biopsy methods affect embryo aneuploidies. Our data indicate that biopsy methods do not affect embryonic aneuploidies, however, simplified biopsy method may improve embryo implantation that may be benefited from reduced embryo manipulations and limited laser applications.…”
Section: Discussionmentioning
confidence: 99%
“…Although aneuploidy is mainly observed in the embryos from patients with advanced maternal ages [1][2][3], it is also very common in the embryos from young patients and oocyte donors [4][5][6][7][8][9]. The frequencies of aneuploid embryos produced by IVF have been widely studied [4][5][6][7][8][9][10][11][12] by examination of all chromosomes with microarray and next generation of sequencing (NGS) through preimplantation genetic testing for aneuploidies (PGT-A) [13][14][15][16][17]. With PGT-A by NGS, not only a whole chromosome aneuploidy can be detected, but also segmental chromosome abnormalities (deletion and duplication) can be detected [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%